2006
DOI: 10.1007/s10519-005-9025-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Anger: Genetic Dominance or Competitive Sibling Interaction

Abstract: The knowledge of the causes and development of anger is still scarce. Previous studies on the sources of variance on Type A Behavior Pattern (TABP) related measures found variable heritability estimates ranging from 0.12 to 0.68, and large differences between MZ and DZ correlations. Some authors considered dominance genetic effects, competitive sibling interaction and sex differences as possible mechanisms to explain the results, but most studies lacked power. The present study uses a large sample of more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 54 publications
3
19
2
1
Order By: Relevance
“…Sex differences in the magnitude of additive and nonadditive genetic influences found in the Dutch twin family study by Rebollo and Boomsma (2006) were not observed in the present sample, however. Several factors might contribute to the discrepancy between the results from the Dutch twin family study and the present findings.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Sex differences in the magnitude of additive and nonadditive genetic influences found in the Dutch twin family study by Rebollo and Boomsma (2006) were not observed in the present sample, however. Several factors might contribute to the discrepancy between the results from the Dutch twin family study and the present findings.…”
Section: Discussioncontrasting
confidence: 79%
“…In the present study, a lack of statistical power associated with small twin samples, especially the small DZ twin samples, may be responsible for a failure to detect sex differences in additive and nonadditive genetic factors. However, one should note that additive and nonadditive genetic estimates for the full scalar sex-limitation model (Model 1) differed in males and females, and the pattern of sex difference was consistent with that found in the study by Rebollo and Boomsma (2006). The SKTR is planning to collect data from siblings of twins to complement DZ twins.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…63,[73][74][75] This genetic influence is seen even for forms of fear that are highly conditioned and context or stimulus dependent, such as the strength of fear conditioning underlying the formation of some phobias. 76 As we have noted above, the regulatory aspects of attention and working memory have been implicated in modulation of negative affect, implying separate but interconnected biological systems for affect and cognitive control.…”
Section: Self-regulation and Genetic Mechanismsmentioning
confidence: 99%